The Impact of Emotional Branding in Customer Buying Behavior in Soft Drink Beverage Industry of Pakistan (KASBIT Business Journal, 2017)
The increasing competition in Pakistan beverage industry specifically in fizzy drink category has made it difficult for marketers to attract and retain customer loyalty. They endeavor higher opportunity cost when planning and investing for promotional activities. Hence, breaking through traditional marketing gimmicks and promotional activities became imperative to influence consumer interest and buying behavior. For which emotional branding pivoted as a significant tool and component that helped revamp advertisement appeal inculcating higher return on investment for companies in industry.The intent behind this study was to determine the impact of emotional branding in customer buying behavior in soft drink beverage industry of Pakistan. The study is quantitative in nature, in which responses from 200 respondents were collected via a survey questionnaire in order to investigate relationship between the two. Various literature sources were studied and critically appraised alongside analyzing collected data through statistical tools like multiple regression analysis, annova and correlation tests in order to acutely gauge research findings that contribute in making distinctions and clear conclusions towards our research objectives. The research results showed the conclusion that there is a positive relationship between emotional branding and buying behavior andemotional branding plays a major role in designing buying behavior, attracting and retaining customers within soft drink industry of Pakistan. Therefore it is recommended that beverage industry should come up with unique practices and instill emotional dimension in its integrated marketing communication strategy in order to establish personalized relationship with customer and distinguish brand identity from number of competitors in industry. The outcome of this research also provides significant insight and valuable recommendations to the local brands who have ventured in the fizzy drink sector in Pakistan to tap lucrative profit margins.
Keywords: emotional branding; buying behavior; customers; soft drinks; beverage industry